Vinylene and benzo[c][1, 2, 5]thiadiazole: effect of the π-spacer unit on the properties of bis(2-oxoindolin-3-ylidene)-benzodifuran-dione containing polymers for n-channel organic field-effect transistors. Issue 68 (20th November 2018) - Do, Thu Trang; Patil, Basanagouda B.; Singh, Samarendra P.; Yambem, Soniya D.; Feron, Krishna; Ostrikov, Kostya (Ken); Bell, John M.; Sonar, Prashant
Abstract : Bottom-gate-top-contact OFET device structure usingPBIBDF-TVT andPBIBDF-TBT based polymer semiconductors. Abstract : Two polymers based on (3 E, 7 E )-3, 7-bis(2-oxoindolin-3-ylidene)benzo[1, 2- b :4, 5- b ′]difuran-2, 6(3 H, 7 H )-dione (BIBDF ) coupled with ( E )-2-(2-(thiophen-2-yl)vinyl)thiophene (TVT) or dithienylbenzothiadiazole (TBT), namelyPBIBDF-TVT andPBIBDF-TBT were synthesized via the Stille coupling reaction. The effect of benzothiadiazole or vinylene-π spacer of the copolymers on optical properties, energy levels, electronic device performance and microstructure were studied. It was found thatPBIBDF-TBT based OFET devices, annealed at 180 °C, showed better performance with the highest electron mobility of 2.9 × 10 −2 cm 2 V s −1 whereasPBIBDF-TVT polymer exhibited 5.0 × 10 −4 cm 2 V s −1 . The two orders of magnitude higher electron mobility ofPBIBDF-TBT overPBIBDT-TVT is a clear indicator of the better charge transport ability of this polymer semiconductor arising from its higher crystallinity and better donor–acceptor interaction.